Determinants of retired customers' interest in using M-Banking at Bank Mandiri taspen with UTAUT - Adelia Tasya Nabila; Trianggoro Wiradinata; Metta Padmalia (Jurnal Mantik, 2026)
This study investigates the determinants of retired customers’ intention to use Movin mobile banking at Bank Mandiri Taspen by applying the Unified Theory of Acceptance and Use of Technology (UTAUT) and examining the role of trust as a mediating variable. Using survey data from 100 retired users and analyzing the data with PLS-SEM, the study finds that performance expectancy and facilitating conditions are the primary drivers of usage intention. In contrast, effort expectancy and social influence do not significantly influence intention. Interestingly, trust does not directly affect intention and does not mediate the relationship between UTAUT constructs and intention to use. These findings suggest that, among retirees, adoption decisions are shaped more by tangible benefits and practical support than by psychological trust mechanisms. The study contributes to the refinement of UTAUT in elderly contexts and offers strategic recommendations for designing user-centered digital banking services tailored to retirees